Territorial defense in a network: audiences only matter to male fiddler crabs primed for confrontation. (11th January 2019) - Darden, Safi K; May, Maggie K; Boyland, Natasha K; Dabelsteen, Torben
Abstract: Territorial contests often occur in the presence of conspecifics not directly involved in the interaction. Actors may alter their behavior in the presence of this audience, an "audience effect, " and audiences themselves may alter their behavior as a result of observing an interaction, a "bystander effect." Previous work has documented these effects by looking at each in isolation, but to our knowledge, none has investigated their interaction; something that is more likely to represent a realistic scenario for species where individuals aggregate spatially. We therefore have a somewhat limited understanding of the extent and direction of these potentially complex indirect social effects on behavior. Here, we examined how audience and bystander effects work in tandem to modify resident male aggressive behavior towards intruders in European fiddler crabs, Afruca tangeri . We found that male crabs with an audience showed greater aggressive behavior towards an intruder compared with males without an audience, but only if they had acted as a bystander to an aggressive signaling interaction prior to the intrusion. Indeed, bystanding during aggressive interactions elevated aggressive responses to intruders maximally if there was an audience present. Our results suggest that bystanding had a priming effect on territory-holding males, potentially by providing information on the immediate level of competition in the local neighborhood, and that same-sex audiences only matter if males have been primed. This study highlights the fundamental importance of considering broader interaction networks in studying real-world dyadic interactions and of including nonvertebrate taxonomic groups in these studies. Abstract : Being part of a social network means that responses to social confrontations are likely to be more complex than they might seem. Indeed, here, we find effects of a wider network of conspecifics on an individual's behavior in male European fiddler crabs. Males became more aggressive toward intruders if their neighbor was watching when they had previously observed an aggressive interaction between their neighbor and a male territory intruder.